Papel do domínio desintegrina da ADAM9 humana na modulação da migração e invasão de células tumorais - Martin, Ana Carolina Baptista Moreno (2011)
Cancer metastasis is the major cause of death, consequently studies to understand the molecular mechanisms involved in this process are essential to the knowledge of this disease. Cell migration and invasion are part of the metastatic process; therefore, molecules that are able to prevent cell migration can be used as model to develop new anti-metastasis drugs. The aim of this project was to study the mechanisms involved on metastasis, then the disintegrin domain of a human ADAM9 (A Disintegin and Metalloprotease), ADAM9D, was cloned in the pGEX-4T-1 plasmid and was expressed in E. coli AD494(DE3) in a soluble and active form. Assays were performed using mama and prostate cancer cells (MDA-MB-231 and DU- 145 respectively) with ADAM9D to verify its functions and the interactions with its ligands. ADAM9D was able to bind to different integrins, β1, αvβ5, αvβ3 and α2 in both cell lines, but only with α6 in DU-145 cells. ADAM9D inhibited cell adhesion to collagen type I in MDAMB- 231 cell, however it did not have the same effect in DU-145 cells. During the proliferation assay ADAM9D did not affect the proliferation in all cell lines tested (MDAMB- 231, DU-145 and human fibroblasts). ADAM9D decreased cell invasion and migration in the transwell and wound healing assays, MMP-2 and MMP-9 had lower expression. ADAM9D decreased cell invasion and migration (wound healing assay), although in the transwell migration assay, ADAM9D increased cell migration and MMP-2/-9 expression. Therefore, this project provides more information about the disintegrin domain of ADAM9 and its role in cell invasion and migration of prostate and mama cancer cells.